2008
DOI: 10.3233/cbm-2008-44-505
|View full text |Cite
|
Sign up to set email alerts
|

Tissue elasticity properties as biomarkers for prostate cancer

Abstract: In this paper we evaluate tissue elasticity as a longstanding but qualitative biomarker for prostate cancer and sonoelastography as an emerging imaging tool for providing qualitative and quantitative measurements of prostate tissue stiffness. A Kelvin-Voigt Fractional Derivative (KVFD) viscoelastic model was used to characterize mechanical stress relaxation data measured from human prostate tissue samples. Mechanical testing results revealed that the viscosity parameter for cancerous prostate tissue is greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
182
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(200 citation statements)
references
References 41 publications
8
182
1
Order By: Relevance
“…Early detection can obviously improve chances of long-term survival. Since 1998, when Krouskop et al confirmed a significant difference in the mechanical behavior between normal and cancerous prostate tissues, elastography has been used as a new imaging technique for the diagnosis of PCa (Hoyta et al, 2008). Elasticity images obtained by quantitative sonoelastography are consistent with the results of mechanical and histological evaluation.…”
Section: Discussionmentioning
confidence: 83%
“…Early detection can obviously improve chances of long-term survival. Since 1998, when Krouskop et al confirmed a significant difference in the mechanical behavior between normal and cancerous prostate tissues, elastography has been used as a new imaging technique for the diagnosis of PCa (Hoyta et al, 2008). Elasticity images obtained by quantitative sonoelastography are consistent with the results of mechanical and histological evaluation.…”
Section: Discussionmentioning
confidence: 83%
“…Viscoelastic properties of human tissues were demonstrated in many examples: the brain and the central nervous system in general [10,44,49], the breast [12], the liver [41,81], the spleen [61], the prostate [36,95], the arteries [13,14], the muscles [31] (see also references for some other human and animal organs tissues [16,50,55,60,69]). Viscoelastic materials obey the following stress-strain relationship:…”
Section: Systems With Memorymentioning
confidence: 99%
“…Eqs. (36), (37), and (43) with α = 3 and variables y = p and z =ṗ produce the full-memory 3D Universal Map…”
Section: α-Families Of Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast lumps examination, for example, in which the hard tissue (lump) embedded in the soft tissues [3], tactile sensation plays a significant role in the first stage of examination. From the clinical data in [7], [11], [12], we can know that lumps are significantly stiffer than surrounding tissues. Such contrast of stiffness can assist doctors in the localization and assessment of lumps during lump examinations, when the doctors' fingertips are in direct contact with the tissue [6].…”
Section: Introduction 1backgroundmentioning
confidence: 99%